Donation Campaign Strategies of Five Islamic Philanthropic Organizations (Qudwah Indonesia, Human Initiative, Rumah Zakat, Dompet Dhuafa, DT Peduli) in Fundraising for the Palestinian Humanitarian Tragedy During October-November 2023 - Lestari, Yuniva Tri (Jurnal Indonesia Sosial Sains, 2025)
This research investigates the donation campaign strategies employed by five Islamic philanthropic organizations (Qudwah Indonesia, Human Initiative, Rumah Zakat, Dompet Dhuafa, and DT Peduli) during the Palestinian humanitarian crisis in October-November 2023. Using a descriptive qualitative approach with Systematic Documentary Review, data was collected through interviews with content managers and observations of digital media platforms, particularly websites. The analysis revealed that each organization tailored its campaign strategies to its internal policies, emphasizing transparency, trust-building, and convenience to encourage donations. The findings show that the donation strategies varied across organizations, with common features such as the use of clear messaging, trust signals, and interactive elements. The study concludes that effective communication strategies, including transparency and ease of access, play a crucial role in increasing public trust and donor engagement.